2015
DOI: 10.1021/acs.jpclett.5b00613
|View full text |Cite
|
Sign up to set email alerts
|

Demystifying PIFE: The Photophysics Behind the Protein-Induced Fluorescence Enhancement Phenomenon in Cy3

Abstract: Protein-induced fluorescence enhancement (PIFE) is a term used to describe the increase in fluorescence intensity observed when a protein binds to a nucleic acid in the proximity of a fluorescent probe. PIFE using the single-molecule dye Cy3 is gaining popularity as an approach to investigate the dynamics of proteins that interact with nucleic acids. In this work, we used complexes of DNA and Klenow fragment and a combination of time-resolved fluorescence and transient spectroscopy techniques to elucidate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
124
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(130 citation statements)
references
References 41 publications
6
124
0
Order By: Relevance
“…The mechanism of fluorescence reduction due to RFS-1/RIP-1 binding to the 5′ end of the filament may represent a modulation of the efficiency of RAD-51-induced PIFE, such that the overall equilibrium PIFE of 5′ Cy3-labeled ssDNA for the RAD-51/RFS-1/RIP-1 complex is lower than that for RAD-51 alone. Recent evidence suggests that Cy3 PIFE arises due to decreased photoisomerization of the dye to the non-fluorescent cis when sterically constrained by protein (Stennett et al., 2015). Indeed, our single molecule fluorescence resonance energy transfer (FRET) studies also established that RFS-1/RIP-1 converts RAD-51-ssDNA filaments to a more flexible conformation (Taylor et al., 2015).…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism of fluorescence reduction due to RFS-1/RIP-1 binding to the 5′ end of the filament may represent a modulation of the efficiency of RAD-51-induced PIFE, such that the overall equilibrium PIFE of 5′ Cy3-labeled ssDNA for the RAD-51/RFS-1/RIP-1 complex is lower than that for RAD-51 alone. Recent evidence suggests that Cy3 PIFE arises due to decreased photoisomerization of the dye to the non-fluorescent cis when sterically constrained by protein (Stennett et al., 2015). Indeed, our single molecule fluorescence resonance energy transfer (FRET) studies also established that RFS-1/RIP-1 converts RAD-51-ssDNA filaments to a more flexible conformation (Taylor et al., 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it was shown that PIFE is specifically due to a reduction in excited-state cis-trans isomerization of Cy3, which normally competes with fluorescence emission (26). Hence, the emission intensity of Cy3 is determined by the degree of steric restriction imposed on the fluorophore by the local environment: Highly restricted environments that inhibit cis-trans isomerization will produce relatively bright emission, whereas unrestricted environments that permit isomerization will lead to relatively weak emission.…”
Section: Discussionmentioning
confidence: 99%
“…For the experiments, we took advantage of an inherent property of the Cyanine 3 fluorophore (Cy3). When Cy3 is covalently attached to DNA it displays a higher fluorescence intensity that depends on the proximity of the fluorophore to a nearby bound protein, a phenomenon termed protein-induced fluorescence enhancement (PIFE) 9,10 (Fig. 1b).…”
Section: Introductionmentioning
confidence: 99%